Redefining Coronavirus: Update on the Impacts of COVID-19 in the Rural Areas of Abia State - Ezinna E Enwereji; Martina C Ezeama; Kelechi O Enwereji (International Journal of Global Health, 2020)
Public health professionals working in rural communities are aware of the health disparities which result from lack of physicians, limited services, and income during the pandemic. Also they are aware that some populations are more vulnerable than others. People in the rural areas are experiencing problems on their physical, social and economic life styles because the pandemic is exacerbating some inequities. Individuals especially women and children in the rural areas are facing barriers in accessing health care services due to lack of resources and availability of health care providers in the communities. With COVID-19, women are less likely to seek services, including sexual and reproductive health services. Such services may be postponed to limit exposure to COVID-19 infection. This is particularly disturbing because in addition to the women maintaining their own health, they are also responsible for taking care of the mental, emotional and physical health needs of their families as well as all domestic responsibilities. As such, women in rural settings face special challenges as a result of these significant roles they play. Therefore, the impacts of COVID-19 are exacerbated on women by virtue of their sex and the roles they play in the family. This is a qualitative study that reviewed the reports of the 36 health care professionals under the aegis of members of COVID-19 committee working in partnership with state government to control, prevent and cushion the effects of COVID-19 in the society. This study is therefore, a summary of the observations of the COVID-19 committee members made up of 10(27.8%) females and 26(72.2%) males. The study focused on exploring how individual lifestyles in the rural areas have been affected in the face of COVID- 19 pandemic by identifying the vulnerabilities in social, political and economic systems which can amplify the impacts of the pandemic. Findings showed that preventive measures like lockdown and social distancing rules, wearing of face mask, hand washing with soap, and environmental cleanliness were not observed. The study noted that health seeking behaviours, sexual and marital life including income, education, employment and social interactions were all negatively affected. Most hospitals were battered and health care professionals boycotted the hospitals for fear of being infected. It was found that lack of health workers in the hospitals caused a good number of individuals to engage in self-medications. Also most pregnant women delivered their babies at home and few with traditional birth attendants. Some of the women who had deliveries at home experienced complications during and after delivery. Unfortunately, the report showed that governments’ financial supports to these women and their family members were insignificant as the government was more concerned with mitigating the spread of COVID-19 than assisting women to have safe deliveries. Therefore, the vulnerable groups especially women, children, and the elderly who experienced threats to their safety and wellbeing as a result of the services that were disrupted during the pandemic, should be assisted so as not to lose their lives to preventable diseases.
Keywords: COVID-19